Using singular value decomposition to investigate degraded Chinese character recognition: evidence from eye movements during reading. (20th March 2013) - Wang, Hsueh‐Cheng; Schotter, Elizabeth R.; Angele, Bernhard; Yang, Jinmian; Simovici, Dan; Pomplun, Marc; Rayner, Keith
Abstract : Previous research indicates that removing initial strokes from Chinese characters makes them harder to read than removing final or internal ones. In the present study, we examined the contribution of important components to character configuration via singular value decomposition. The results indicated that when the least important segments, which did not seriously alter the configuration (contour) of the character, were deleted, subjects read as fast as when no segments were deleted. When the most important segments, which are located in the left side of a character and written first, were deleted, reading speed was greatly slowed. These results suggest that singular value decomposition, which has no information about stroke writing order, can identify the most important strokes for Chinese character identification. Furthermore, they also suggest that contour may be correlated with stroke writing order.